2015
DOI: 10.1111/lam.12485
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of methicillin-resistant Staphylococcus aureus from small ruminants and their meat at slaughter and retail level in Greece

Abstract: This study is the first report on methicillin-resistant Staphylococcus aureus in small ruminants and their meat at slaughter level in Greece, elucidating a possible vehicle food for transmission to humans. These results suggest that human or animal sources could be involved in meat contamination and thus sources of contamination require investigation to control the dispersion of MRSA in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
10
9
1
Order By: Relevance
“…S. aureus and MRSA isolation rates from animals and carcass’ surfaces observed in this study are in accordance with another recent study from Greece conducted with samples from small ruminants and their carcasses at slaughter and retail level (Sergelidis et al, ). However, our results are lower as compared to data from Velasco, Sherwood, Rojas‐Garcia, and Logue () (40.6%) and Waters et al (), who revealed S. aureus prevalence of 47% in 136 samples of raw meat and poultry.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…S. aureus and MRSA isolation rates from animals and carcass’ surfaces observed in this study are in accordance with another recent study from Greece conducted with samples from small ruminants and their carcasses at slaughter and retail level (Sergelidis et al, ). However, our results are lower as compared to data from Velasco, Sherwood, Rojas‐Garcia, and Logue () (40.6%) and Waters et al (), who revealed S. aureus prevalence of 47% in 136 samples of raw meat and poultry.…”
Section: Resultssupporting
confidence: 93%
“…Multiple studies demonstrating the high prevalence of multidrug-resistant S. aureus, including ST398, among livestock in the European Union, Canada, and United States have been reported (Khanna, Friendship, Dewey, & Weese, 2008;Smith & Pearson, 2011). In Greece, even though S. aureus clones disseminated in the community and hospitals among humans are well characterized, limited data are available concerning clonal spread in food production chain (including animals, equipment, meat products, abattoir personnel) that may influence the epidemiology of staphylococcal infections in the community and hospital environments (Drougka et al, 2016(Drougka et al, , 2014(Drougka et al, , 2012Sarrou et al, 2015;Sergelidis et al, 2015).…”
mentioning
confidence: 99%
“…However, closely related or identical isolates were detected in different farms and probably this is evidence that certain genotypes dominate. Same results had been published from France (Vautor et al 2003), from Spain and Italy (Goñi et al 2004;Spanu et al 2013) and recently from Greece (Zdragas et al 2015). Diversity in epidemiologically unrelated strains has been observed several times (Campos et al 2009; Otero et al 2013; Zdragas et al 2015) and the same was observed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting that 83% of S. aureus isolates were susceptible to all the antimicrobials tested. The penicillin resistance level of 17% is similar to some other reports (Mørk et al 2005;Zdragas et al 2015) but low compared with the 96•3% elsewhere (Gündogȃn et al 2006). This is a strong evidence of the low pressure of antibiotics in sheep and goat industry in Greece.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation